Impact of omitting post-transplant minidose-methotrexate doses in allogeneic hematopoietic cell transplantation. Issue 7 (7th June 2022) - Lin, Andrew; Brown, Samantha; Maloy, Molly; Ruiz, Josel D.; Devlin, Sean; DeRespiris, Lauren; Proli, Anthony; Jakubowski, Ann A.; Papadopoulos, Esperanza B.; Sauter, Craig S.; Tamari, Roni; Castro-Malaspina, Hugo; et al.
Abstract: Given prophylactic methotrexate (MTX) is often held in the setting of toxicity we investigated the impact of omitting minidose-MTX dose(s). Outcomes were compared between patients who had 1–3 doses omitted and those who received all four planned doses of minidose-MTX. Of 370 consecutive patients, 50 had MTX dose(s) omitted. When MTX was omitted, initial management was mycophenolate mofetil (MMF; 36/50 patients) with or without corticosteroids (14/50 patients). Rates of grade 3–4 acute GVHD were similar between groups. Omission of minidose-MTX resulted in an increased risk of chronic GVHD (cGVHD; HR 2.27; p = .024) and decreased overall survival (HR 1.61; p = .024). However, other transplant-related outcomes were comparable. In summary, omission of minidose-MTX doses was not associated with an increased risk of acute GVHD when an alternative was added (e.g. MMF ± corticosteroids). This did not abrogate the increased risk of cGVHD or decreased overall survival.